2016
DOI: 10.1063/1.4962908
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of state-resolved information from systems with a fractional number of electrons within the framework of time-dependent density functional theory

Abstract: The determination of the state-resolved physical information within the framework of time-dependent density functional theory has remained a widely open question. We demonstrated the ability to extract the state-resolved probability from the knowledge of only the time-dependent density, which has been used as the basic variable within the time-dependent density functional theory, with the help of state-resolved single-electron capture experiments for collisions of protons on helium in the energy range of 2-100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A spin-dependent ALDA calculation with self-interaction corrections included, on the other hand, showed better agreement with the experimental data in the low-energy range [23]. State-resolved TDDFT capture results were reported in [43].…”
Section: Energy Loss Bgm Bgm; Response Sc-ccc Bailey 15mentioning
confidence: 75%
“…A spin-dependent ALDA calculation with self-interaction corrections included, on the other hand, showed better agreement with the experimental data in the low-energy range [23]. State-resolved TDDFT capture results were reported in [43].…”
Section: Energy Loss Bgm Bgm; Response Sc-ccc Bailey 15mentioning
confidence: 75%
“…Non-stationary populations during field-free propagation was first discussed in the TDHF method in nuclear physics [117,[119][120][121], and later, in time-dependent density functional theory in atomic and molecular physics [122][123][124]. Padmanaban and Nest [125] showed that the energy eigenvalues of stationary states, calculated from the Fourier transform of the autocorrelation function of an MCTDHF wave function, depend on the laser pulse employed in the excitation and ascribed the dependence to the nonlinearity in the equations of motion.…”
Section: Introductionmentioning
confidence: 99%